UVB radiation generates sunburn pain and affects skin by activating epidermal TRPV4 ion channels and triggering endothelin-1 signaling - Moore, Carlene (National Academy of Sciences, 2013)
At our body surface, the epidermis absorbs UV radiation. UV overexposure leads to sunburn with tissue injury and pain. To understand how, we focus on TRPV4, a nonselective cation channel highly expressed in epithelial skin cells and known to function in sensory transduction, a property shared with other transient receptor potential channels. We show that following UVB exposure mice with induced Trpv4 deletions, specifically in keratinocytes, are less sensitive to noxious thermal and mechanical stimuli than control animals. Exploring the mechanism, we find that epidermal TRPV4 orchestrates UVB-evoked skin tissue damage and increased expression of the proalgesic/algogenic mediator endothelin-1. In culture, UVB causes a direct, TRPV4-dependent Ca(2+) response in keratinocytes. In mice, topical treatment with a TRPV4-selective inhibitor decreases UVB-evoked pain behavior, epidermal tissue damage, and endothelin-1 expression. In humans, sunburn enhances epidermal expression of TRPV4 and endothelin-1, underscoring the potential of keratinocyte-derived TRPV4 as a therapeutic target for UVB-induced sunburn, in particular pain.